Tribological behaviour of Ti3C2T x nano-sheets: Substrate-dependent tribo-chemical reactions - Alberto Rota; Nicolas Bellina; Bo Wang; Andreas Rosenkranz (Friction)
Abstract MXenes, a newly emerging class of layered two dimensional (2D) materials, are promising solid lubricants due to their 2D structure consisting of weakly-bonded layers with a low shear strength and ability to form beneficial tribo-layers. This work aims at evaluating for the first time MXenes lubrication performance and tribofilm formation ability on different metallic substrates (mirror-lapped Fe and Cu discs). After depositing MXenes via ethanol (1 wt%) on the substrates, pronounced differences in the resulting substrate-dependent frictional evolution are observed. While MXenes are capable to reduce friction for both substrates after the full evaporation of ethanol, MXenes lubricating effect on Cu is long-lasting, with a 35-fold increased lifetime compared to Fe. Raman spectra acquired in the wear-tracks of the substrates and counter-bodies reveal notable differences in the friction-induced chemical changes depending on the substrate material. In case of Fe, the progressive failure of MXenes lubrication generates different Fe oxides on both the substrate and the ball, resulting in continuously increasing friction and a poor lubrication effect. For Cu, sliding induces the formation of a Ti3C2-based tribofilm on both rubbing surfaces, enabling a long-lasting lubricating effect. This work boosts further experimental and theoretical work on MXenes involved tribo-chemical processes.